Peningkatan Skill Leadership Mahasiswa melalui Latihan Dasar Kepemimpinan mahasiswa (LDKM) - Basri; Hasnani (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
Leadership is one of the essential competencies that must be possessed by students as future leaders. The Student Basic Leadership Training (LDKM) is one of the effective training methods to develop this ability. This article aims to analyze the role of LDKM in enhancing students' leadership skills. Using a descriptive qualitative approach and literature review, it was found that LDKM has a significant impact on the development of leadership character, communication, conflict management, and decision-making abilities. These findings indicate that leadership training such as LDKM should be made a mandatory program in the development of students' soft skills.